Analysis of Capacity and Phase Composition of Chromotitanazing Surface - oglu Abbasov, E.O. (Physics and Chemistry of Solid State, 2015)
The article deals with the investigation of phase composition and capacity of chromotitanazing surface of steel of 25X5MA. Components made of steel with the coatings applied ШХ-15 and 12XH3A were taken as comparison. Absence phase of coatings Cr23C6 and Cr7C3 on the surface layer was determined. Main phase of the layer is textured structure of Nitride chrome Cr2N. As compared with diffusion coatings applied Ion plasma coatings do not provide bearing capacity of components at their low thickness.